Placing practitioner knowledge at the center of teacher education : rethinking the policies and practices of the education doctorate - Macintyre Latta, Margaret, 1955-; Wunder, Susan A. (Education policy in practice., 2012)
Rethinking the Education Doctorate so that practitioner knowledge is at the center of programmatic concern in teacher education raises provocative education policy/practice considerations. Participants in the national Carnegie Project on the Education Doctorate (CPED) are doing just this. Their accounts of rethinking what counts as educational knowledge and their reconsideration of the roles of teacher educators, scholar-practitioners, students, policy makers, and others are illuminated in this book. Asserting the primacy of practitioner knowledge, the book generates a rich and complex terrain of issues and considerations that participating CPED institutions navigate as multiple technical, normative, and political questions at the crux of educator preparation, professional growth, and control of their field. And, it is this terrain that calls attention to the nature of practitioner knowledge and its inherent potential for redirecting, mediating, and generating education policy. Conversations within and across national and local levels orient away from technical means-ends "what works" questions alone, and open into normative and political questions about educational value and professional action.In documenting the largest, most coordinated effort to rethink the educational doctorate in a century of such efforts, this book will interest teacher educators and programs engaged in pre-service and graduate level teacher education, practicing K-16 teachers, and education policy/practice interest groups and individuals. Illustrating a policy development method that is neither top-down nor necessarily 'grass roots', it also invites the interest of other educational sectors. Additionally, as CPED implementation contexts value interdisciplinarity, multiple methodological perspectives, and interactions and deliberations across interests, the lived consequences and significances of doing so are mapped out and, as such, hold much potential for policy/practice intersections within manifold education settings, and beyond, to settings of all kinds invested in the primacy of practitioner knowledge. Thus, a core goal of this volume is to broach these considerations with a broad readership.